System to measure torsion modulus of polymers using the deformation energy method - Pintão,Carlos Alberto Fonzar (2019)
Abstract This paper presents an alternative method to measure the torsion modulus, G, for samples of polymers. We constructed a measurement system with a force sensor (FS) and a rotational movement sensor (RMS) to obtain a relationship between force (F) and torsion angle (θ). An expression that could return the value of G was deduced using the deformation energy method. This technique is nondestructive and independent of knowing the value of Poisson’s ratio. Samples with different diameters of polytetrafluoroethylene (PTFE) were submitted to quasi-static torsion at the same aspect ratio. The aim was to present and validate the use of the technique for a known polymer. The approximate value of 350 MPa of the torsion modulus G was found for PTFE samples. As the values obtained are within the limits found in the literature, the technique can be used to study samples of polymers and other materials.